Impaired mitochondrial integrity and compromised energy production underscore the mechanism underlying CoASY protein-associated neurodegeneration. - Shao, Y.; Hu, J.; Yan, K.; Zheng, K.; Sha, W.; Wang, J.; Wu, J.; Huang, Y. (Cellular and molecular life sciences. CMLS, 2025)
Coenzyme A (CoA) is a crucial metabolite involved in various biological processes, encompassing lipid metabolism, regulation of mitochondrial function, and membrane modeling. CoA deficiency is associated with severe human diseases, such as Pantothenate Kinase-Associated Neurodegeneration (PKAN) and CoASY protein-associated neurodegeneration (CoPAN), which are linked to genetic mutations in Pantothenate Kinase 2 (PANK2) and CoA Synthase (CoASY). Although the association between CoA deficiency and mitochondrial dysfunction has been established, the underlying molecular alterations and mechanisms remain largely elusive. In this study, we investigated the detailed changes resulting from the functional decline of CoASY using the Drosophila model. Our findings revealed that a reduction of CoASY in muscle and brain led to degenerative phenotypes and apoptosis, accompanied by impaired mitochondrial integrity. The release of mitochondrial DNA was notably augmented, while the assembly and activity of mitochondrial electron transport chain (ETC) complexes, particularly complex I and III, were diminished. Consequently, this resulted in decreased ATP generation, rendering the fly more susceptible to energy insufficiency. Our findings suggest that compromised mitochondrial integrity and energy supply play a crucial role in the pathogenesis associated with CoA deficiency, thereby implying that enhancing mitochondrial integrity can be considered a potential therapeutic strategy in future interventions.